BIM leadership theory for organisational BIM transformation - Olugboyega, Oluseye (Frontiers in Built Environment, 2022)
Construction firms are struggling to stay in business as a result of BIM’s new and compelling business model and potential. As a result, businesses must adapt their current operations to the BIM paradigm by developing new organisational leadership capabilities. While such BIM leadership capacity is critical in designing, advancing, and driving a competitive and successful BIM transformation, BIM researchers have largely ignored it. Thus, this research explores the leadership capacities to drive BIM transformation in construction organisations in order to determine whether it will provide a leadership model as a solution to the leadership demands of organisations undergoing BIM transformation. The study design was a confirmatory sequential mixed methods research strategy that included a theoretical framework established through literature synthesis, qualitative grounded theory, and artificial intelligence (AI)-based modelling. Following the GT analysis, leadership capacity to drive organisational BIM transformation equates to the capability to develop a BIM-friendly leadership orientation, build a BIM-focused leadership procedure, perform BIM-related leadership responsibilities, generate a BIM-enabled leadership environment, and reach maturity within the realms of these strengths. The overall results of the AI-based modelling demonstrated that the acceptable capacity needed by the leadership that is pivoting organisational BIM transformation is the capability to coordinate functions, individuals, and transition alignment; produce BIM-related policies and a positive atmosphere for BIM implementation; and impartiality in recruiting individuals for BIM leadership roles. The study’s findings have implications for targeting key initiatives that might aid leaders in constructing adaptation strategies for organisational BIM transformation.